Cultural Heritage Gaming: Effects of Human Cognitive Styles on Players' Performance and Visual Behavior - Raptis, George E.; Fidas, Christos; Avouris, Nikolaos (Adjunct Publication of the 25th Conference on User Modeling, Adaptation and Personalization - UMAP '17, 2017)
Common design practices of current cultural heritage activities barely take into account the contextual, cultural, and cognitive characteristics of visitors. Bearing in mind that information processing is substantial in such activities, this paper investigates the interplay among human cognitive differences and cultural heritage gaming activities towards players' performance and visual behavior. Three user studies were conducted under the field dependence/independence theory, which underpin cognitive differences in visual perceptiveness and contextual information handling. Findings are expected to provide useful insights for practitioners and researchers with the aim to design playful cultural activities tailored to the users' cognitive preferences.